2018
DOI: 10.1002/chem.201800389
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonal Clickable Iron Oxide Nanoparticle Platform for Targeting, Imaging, and On‐Demand Release

Abstract: A versatile iron oxide nanoparticle platform is reported that can be orthogonally functionalized to obtain highly derivatized nanomaterials required for a wide variety of applications, such as drug delivery, targeted therapy, or imaging. Facile functionalization of the nanoparticles with two ligands containing isocyanate moieties allows for high coverage of the surface with maleimide and alkyne groups. As a proof-of-principle, the nanoparticles were subsequently functionalized with a fluorophore as a drug mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…3). To this end, thermo-reversible Diels−Alder (DA) reactions and thermo-labile azo-linkers have been described [13,[35][36][37][38]. Among the drawbacks associated to this strategy, the possible decrease of the biological activity of the drug when covalently attached to the MNP, and the relatively high local temperatures (80-90°C) that must be reached in order to effectively break the bonds, must be taken into account.…”
Section: Caused By Bond Breakmentioning
confidence: 99%
“…3). To this end, thermo-reversible Diels−Alder (DA) reactions and thermo-labile azo-linkers have been described [13,[35][36][37][38]. Among the drawbacks associated to this strategy, the possible decrease of the biological activity of the drug when covalently attached to the MNP, and the relatively high local temperatures (80-90°C) that must be reached in order to effectively break the bonds, must be taken into account.…”
Section: Caused By Bond Breakmentioning
confidence: 99%
“…Moreover, a proof-of-concept for pyrene release by external magnetic field showed potential as a controlled drug delivery platform. 150 In 2017, biotinylated-PEG-PLGA NPs containing DOX (BPNP) improved 4T1 cellular uptake in flow cytometry compared with non-biotinylated DPNP (MFI of 214 vs 113) and were more cytotoxic after 24 hours (IC50: 91.5 nM vs 131.8 nM). 121…”
Section: Examples Of Cuaacmentioning
confidence: 99%
“…MNPs are a type of MRI contrast agents with multifunctional properties that are considered interesting probes for their co-localization in specific tissues, such as some tumors. Guldris and co-workers [ 56 , 57 , 58 ] and Keasberry et al [ 59 ] reported that proper designs of iron oxide MNPs can significantly enhance the diagnostic capability of MRI when compared to other nanostructured Fe-based contrast agents currently available. The most common magnetic labels used in vivo are based on gadolinium (Gd) complexes and iron oxide magnetic nanoparticles (Fe 3 O 4 ).…”
Section: Magnetic Nanoparticlesmentioning
confidence: 99%